The national application of inclusive international framework of sport and athlete - Kinugasa, T.; Funasaki, K.; Fujiwara, A.; Morley, E.; Gulbin, J. (Journal of High Performance Sport, 2019)
After the literature review, there are various models of athlete development pathway, but the international framework, FTEM (Foundation, Talent, Elite, Mastery), is a useful framework for understanding the stages of athlete development from grassroots to the podium with practical application by National Federations (NFs). We propose an inclusive and evidence-informed framework "The Japanese FTEM". The unique framework is applicable nationally to the whole of sport for bridging the gap between theory and practice of athlete development by taking into account the cultural and social context in Japan. The Japanese FTEM is an inclusive and evidence-informed framework in which sport and athlete development are integrated. It can be used as a guide for practitioners of athlete development such as NFs to co-design a sport-specific mid- to long-term development plan for sustainable success.